2004
DOI: 10.1016/j.bbmt.2004.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of granulocyte colony-stimulating factor on marrow- and blood-derived hematopoietic and immune cell populations in healthy human donors

Abstract: A recent phase III trial comparing granulocyte colony-stimulating factor (G-CSF)-stimulated bone marrow (G-BM) and G-CSF-mobilized peripheral blood (G-PB) in matched sibling allograft recipients showed that G-BM produced a similar hematologic recovery but a reduced incidence of extensive chronic graft-versus-host disease, indicating differences in the cell populations infused. As a first step toward identifying these differences, we treated a group of healthy adult humans with 4 daily doses of G-CSF 10 microg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 50 publications
2
27
1
Order By: Relevance
“…After G-CSF stimulation, the number of BM CD34 ϩ cells increases 1.4-to 1.7-fold, the number of colony-forming cells 3-fold and the number of long-term culture-initiating cells 50-to 90-fold. 43 Furthermore, G-CSF exerts an intense immunoregulatory effect on BM T cells by down-regulating the expression of adhesion and CD28/B7 molecules and by increasing the absolute number of DC2 APCs favoring a T-cell shift from Th1-to Th2-type cells and inducing an higher production of IL-4 and IL-10 anti-inflammatory cytokines. [44][45][46][47] In transplantations from HLA identical siblings, engraftment of G-CSF-primed BM cells is faster, with an incidence of Ն grade II acute GVHD of only 6.3%.…”
Section: Discussionmentioning
confidence: 99%
“…After G-CSF stimulation, the number of BM CD34 ϩ cells increases 1.4-to 1.7-fold, the number of colony-forming cells 3-fold and the number of long-term culture-initiating cells 50-to 90-fold. 43 Furthermore, G-CSF exerts an intense immunoregulatory effect on BM T cells by down-regulating the expression of adhesion and CD28/B7 molecules and by increasing the absolute number of DC2 APCs favoring a T-cell shift from Th1-to Th2-type cells and inducing an higher production of IL-4 and IL-10 anti-inflammatory cytokines. [44][45][46][47] In transplantations from HLA identical siblings, engraftment of G-CSF-primed BM cells is faster, with an incidence of Ն grade II acute GVHD of only 6.3%.…”
Section: Discussionmentioning
confidence: 99%
“…13 Transplantation experiments to examine the properties of individual repopulating cells have further suggested that hematopoietic recovery in mice can be carried out by a very small number of clones when grafts of freshly isolated murine cells are transplanted. [14][15][16][17] In humans, it seems much less likely that the neutrophils and platelets produced immediately after transplantation would represent clonal populations for a number of reasons.…”
Section: Org Frommentioning
confidence: 99%
“…Thereby, G-CSF activates progenitor cell releasing factors such as neutrophile elastases and matrix-metalloproteinase to release the stem cells from the bone marrow. 13 Within the bone marrow, activated elastases were shown to cleave receptors and integrins. Bone marrow stromal cells express vascular cell adhesion molecule (VCAM)-1/CD 106 that adheres to the integrin ␣4␤1 or very late antigen-4 (VLA-4) expressed by HSCs and EPCs.…”
mentioning
confidence: 99%